ADAR RNA editing in innate immune response phasing, in circadian clocks and in sleep - Sinigaglia, Ketty; Wiatrek, Dagmara; Khan, Anzer; Michalik, David; Sambrani, Nagraj; Sedmík, Jiří; Vukić, Dragana; O'Connell, Mary A; Keegan, Liam P (Biochimica et biophysica acta. Gene regulatory mechanisms, 2019)
Adenosine deaminases acting on RNA (ADARs) convert adenosine to inosine in dsRNA. ADAR editing in pre-mRNAs recodes open reading frames and alters splicing, mRNA structure and interactions with miRNAs. Here, we review ADAR gene expression, splice forms, posttranslational modifications, subcellular localizations and functions of ADAR protein isoforms. ADAR1 edits cellular dsRNA to prevent aberrant activation of cytoplasmic antiviral dsRNA sensors; ADAR1 mutations lead to aberrant expression of interferon in Aicardi Goutières syndrome (AGS), a human congenital encephalopathy. We review related studies on mouse Adar1 mutant phenotypes, their rescues by preventing signaling from the antiviral RIG-I-like Sensors (RLRs), as well as Adar1 mechanisms in innate immune suppression and other roles of Adar1, including editing-independent effects. ADAR2, expressed primarily in CNS, edits glutamate receptor transcripts; regulation of ADAR2 activity in response to neuronal activity mediates homeostatic synaptic plasticity of vertebrate AMPA and kainite receptors. In Drosophila, synapses and synaptic proteins show dramatic decreases at night during sleep; Drosophila Adar, an orthologue of ADAR2, edits hundreds of mRNAs; the most conserved editing events occur in transcripts encoding synapse-associated proteins. Adar mutant flies exhibit locomotion defects associated with very increased sleep pressure resulting from a failure of homeostatic synaptic processes. A study on Adar2 mutant mice identifies a new role in circadian rhythms, acting indirectly through miRNAs such as let-7 to modulate levels of let-7 target mRNAs; ADAR1 also regulates let-7 miRNA processing. Drosophila ADAR, an orthologue of vertebrate ADAR2, also regulates let-7 miRNA levels and Adar mutant flies have a circadian mutant phenotype.
Keywords: RNA Editing; cirkadiánní hodiny; spánek; Circadian rhythm; editace RNA; Immunity, Innate; Sleep; Circadian Clocks; Adenosine Deaminase; přirozená imunita; ADAR; Epitranscriptome; zvířata; Humans; Innate immunity; microRNA; dsRNA; RNA editing; adenosindeaminasa; lidé; Animals